Who captures whom? Regulatory misperceptions and the timing of cognitive capture - Georg Rilinger (Regulation & Governance, 2021)
To explain cognitive capture, economic sociologists often examine the structure of relationships between regulators and market participants. This paper argues that the nature of regulators' misperception should be subject to analysis as well. Different types of misperceptions develop over timelines of varying lengths. Depending on the misperception, different sets of relationships and parties may therefore be the cause of regulators' capture. The paper illustrates this point with a case study of regulators' failure to detect pervasive market power in California's electricity markets between 1998 and 2001. Existing explanations focus on sellers' short-term attempts to distract regulators from widespread evidence of market power. Using data from three archives and in-depth interviews, I show that the regulators did not fall prey to such “information problems.” Instead, their misperception resulted from a more foundational “worldview problem.” This error affects regulators' basic conception of the marketplace and can be traced to earlier and more gradual forms of influence exerted by utilities that, ironically, would become the victims of market power.
Keywords: 330; California energy crisis; cognitive capture; economic sociology; regulatory capture; regulatory dialectic